ANALISIS KEUNTUNGAN USAHA KEDAI KOPI â€œBABA BUDANâ€ JALAN RODA DI KOTA MANADO - William Marcel Tanwijaya; Ribka Magdalena Kumaat; Caroline B. D. Pakasi (Sam Ratulangi University, 2018)
This study aims to analyze the profitability of the coffee shop business